Association between retinol intake and periodontal health in US adults - Shenyue Zhou; Juan Chen; Ruoyan Cao (BMC, 2023)
Abstract Background Inflammation and oxidative stress are two hallmarks of periodontitis. Retinol is an antioxidant and suppresses expression of pro-inflammatory factors. However, the evidence for an association between retinol intake and periodontitis is limited. Thus, the aim of this study is to assess the association between retinol intake and periodontal health. Methods Data used in this cross-sectional study from the National Health and Nutrition Examination Survey (NHANES) 2009-2014 (n = 9081). Dietary intake of retinol was measured based on two 24-h dietary recall interviews. The category of periodontitis was defined by the CDC/AAP according to clinical periodontal parameters. Univariate and multivariate logistic regression analyses were applied to investigate the relationship between retinol intake and the risk of periodontitis. Results Compared with the lowest tertile, individuals in the highest tertile of retinol intake were less likely to be periodontitis (ORtertile3vs1 = 0.79, 95% CI: 0.65-0.96). The association was still significant in populations who were less than 60 years old (ORtertile3vs1 = 0.80, 95% CI: 0.65-0.97), non-Hispanic black (ORtertile3vs1 = 0.62, 95% CI: 0.42-0.94), PI ≤ 1.3 (ORtertile3vs1 = 0.72, 95% CI: 0.55-0.93), 1.3 < PI ≤ 3.5 (ORtertile3vs1 = 0.70, 95% CI: 0.55-0.89), non-smoker (ORtertile3vs1 = 0.63, 95% CI: 0.48-0.81), obesity (ORtertile3vs1 = 0.68, 95% CI: 0.49-0.94) and who had not diabetes mellitus (ORtertile3vs1 = 0.79, 95% CI: 0.65-0.95) or had hypertension (ORtertile3vs1 = 0.63, 95% CI: 0.47-0.84). Conclusion Retinol intake is inversely associated with poor periodontal health in US adults.